Nonadherence Factors and Sociodemographic Characteristics of HIV-Infected Adults Receiving Antiretroviral Therapy in Nnamdi Azikiwe University Teaching Hospital, Nnewi, Nigeria. (28th November 2013) - Okoronkwo, Ijeoma; Okeke, Uchenna; Chinweuba, Anthonia; Iheanacho, Peace
Abstract : Adherence to treatment instructions with antiretroviral therapy (ART) is very crucial for successful treatment outcome. However, sticking to treatment instructions pose-great challenges to HIV/AIDS patients. This cross-sectional study was on HIV infected adults attending ART clinic in Nigeria to explore nonadherence factors in relation to their socioeconomic characteristics. Validated structured questionnaire was administered to 221 participants. Results showed a high nonadherence rate of 85.1%. The commonest occurring factors of non-adherence were forgetfulness (53.8%), busy schedule (38.8%), side effects of drugs (31.9%), and stigma (31.9%). Males were more likely to complain from busy schedule, feeling healthy, fear of partner disclosure, long waiting period, and long term regimen. Patients with no formal education were more likely to attribute non-adherence to poor communication, side effects of drugs, and stigma. Employed patients seemed to miss their drugs more than the unemployed and artisans. The high non-adherence rate has serious implications for the control of HIV in infected individuals and management of HIV in general. Nurses should intensify efforts on patient education and counseling.